Bacteriology of Infection in Severe Acute Pancreatitis - Noor, Mohd T; Radhakrishna, Yellapu; Kochhar, Rakesh; Ray, Pallab; Wig, Jai Dev; Sinha, Saroj K; Singh, Kartar (JOP. Journal of the Pancreas, 2011)
Context Severe acute pancreatitis is associated with high mortality with infectious complications being the most common cause of mortality. Objective To analyze the prevalence and characteristics of pancreatic and extrapancreatic infection in patients with severe acute pancreatitis. Design Prospective study over a one-year period. Patients Fifty-one consecutive patients with severe acute pancreatitis. Setting Tertiary care centre, Northern India. Main outcome measures The presence of pancreatic and extrapancreatic infections were noted in consecutive patients with severe acute pancreatitis and their effect on disease outcome was assessed. Results Pancreatic infection was noted in 19 (37.3%) patients; 14 (27.5%) patients had monomicrobial and 5 (9.8%) patients had polymicrobial infections. In the first week of hospitalization, all positive 6/6 (100%) cultures grew Escherichia coli, in the second week 5/8 (62.5%) grew Escherichia coli while after the second week, 2/5 (40.0%) cultures grew Escherichia coli. A total of 32 (62.7%) patients had evidence of extrapancreatic infections, with 53 positive cultures. Fifteen (29.4%) patients had monomicrobial infections while 17 (33.3%) had polymicrobial infections. The most common site was blood together with intravenous site with 21 positive cultures in 16 patients. Staphylococcus aureus was most commonly isolated in the blood cultures. There was a statistically significant increase in mortality with pancreatic (P=0.003) and extrapancreatic (P=0.041) infections. The antibiotic sensitivity pattern showed that most of the bacteria were sensitive to beta lactum antibiotics, aminoglycosides and imipenem. Conclusion Pancreatic infections are more often monomicrobial with a shift from gram-negative to gram-positive as the pancreatitis progressed. Extrapancreatic infections are more often polymicrobial; most commonly, the blood stream is invaded by gram-positive bacteria. Image: Escherichia coli (Wikimedia Commons by Mattosaurus)